EFFECTIVENESS OF THE “TEMAN SUKA BESTE” INNOVATION IN TRANSFORMING PUBLIC SERVICES AT THE INSPECTORATE OF BALANGAN REGENCY - Muhammad Rosi; Irza Setiawan (Antis Publisher, 2026)
Objective: This study analyzes the effectiveness of implementing the “Teman Suka Beste” innovation (an acronym for Sistem Layanan Surat Keterangan Bebas Temuan or Clear-of-Audit-Findings Certificate Service System) by the Regional Inspectorate of Balangan Regency. The research focuses on evaluating the achievement of innovation goals in enhancing the efficiency, transparency, and accountability of services provided to Civil Servants (ASN). Method: The research employs a qualitative case study approach. Data were collected from official documentation, institutional websites, and media reports regarding program socialization. Results: The results indicate that “Teman Suka Beste” has successfully transformed the service from a convoluted conventional model into an online system that streamlines bureaucracy and reduces processing time, with a completion target of one day. This innovation aligns with the new paradigm of the Government Internal Supervisory Apparatus (APIP) as a provider of quality assurance and a consulting partner. The primary challenges identified include the need for continuous socialization and integration with other internal oversight systems, such as the Hawasi application. Novelty: “Teman Suka Beste” represents an effective breakthrough that supports the acceleration of bureaucratic reform and good governance at the regional level through the transformation of the Clear-of-Audit-Findings Certificate service into a streamlined digital system.